2013
DOI: 10.1111/nhs.12057
|View full text |Cite
|
Sign up to set email alerts
|

American rural women's exercise self‐efficacy and awareness of exercise benefits and safety during pregnancy

Abstract: Though the positive link between physical activity and maternal health is well documented, physical activity declines during pregnancy and, internationally, rural mothers are less likely than urban mothers to engage in physical activity. Some evidence suggests that self-efficacy is related to sustained engagement in physical activity. The purpose of this study was to examine self-efficacy, perceived benefits, and knowledge of safe exercise among 88 rural pregnant women in a southeastern region of the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 25 publications
2
18
0
1
Order By: Relevance
“…18 A previous study evaluated the self-efficacy for exercise during pregnancy among women who are pregnant who were living in rural communities in America. 19 Similar to the current study, the majority of the women reported decreasing energy levels as a concern for engaging in prenatal exercise, and this in turn reduced their self-efficacy for engaging in physical activity. 19 A decrease in energy levels is a concern for women because of the already increased level of fatigue they may be experiencing during pregnancy, especially during the first trimester.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…18 A previous study evaluated the self-efficacy for exercise during pregnancy among women who are pregnant who were living in rural communities in America. 19 Similar to the current study, the majority of the women reported decreasing energy levels as a concern for engaging in prenatal exercise, and this in turn reduced their self-efficacy for engaging in physical activity. 19 A decrease in energy levels is a concern for women because of the already increased level of fatigue they may be experiencing during pregnancy, especially during the first trimester.…”
Section: Discussionsupporting
confidence: 72%
“…19 Similar to the current study, the majority of the women reported decreasing energy levels as a concern for engaging in prenatal exercise, and this in turn reduced their self-efficacy for engaging in physical activity. 19 A decrease in energy levels is a concern for women because of the already increased level of fatigue they may be experiencing during pregnancy, especially during the first trimester. 20 Interestingly, improvement in energy levels is one of the known benefits of engaging in exercise during pregnancy, 21 along with an improvement in mood, 21 decreased risk of prenatal depression, 22 and improved sleep.…”
Section: Discussionsupporting
confidence: 72%
“…the awareness that exercise is beneficial during pregnancy may be unique to this group of women considering that many were college-educated. Melton et al [22] reported that in a sample of 88 American rural pregnant women (60.2% white), only 56.8% were convinced that they could exercise without consulting a physician and 61.4% knew that exercise could help prevent or treat gestational diabetes. related, in a study of 57 nulliparous pregnant women, 81% received some type of advice on PA at 16 weeks gestation; however, 67% of that group obtained most of their infor-mation from books and magazines, while 47% from friends and family, compared with only 18% from health professionals [23].…”
Section: Resultsmentioning
confidence: 99%
“…), healthcare providers and health professionals may be more effective in promoting their message. Further, according to Melton et al [22], only 21.6% of pregnant American rural women knew that exercise could increase energy levels. thus, it may be possible to inform women about the immediate energizing effects of exercise to help overcome the most commonly reported barrier of lacking energy.…”
Section: Resultsmentioning
confidence: 99%
“…For example, poor health, higher body mass index (BMI), advancing age, and depression have been negatively associated with physical activity levels in rural women (Olsen, 2013). Low income rural mothers, as well as pregnant and older rural women, have reported lack of knowledge of physical activity guidelines and health benefits (Atkinson, Billing, Desmond, Gold, & Tournas-Hardt, 2007;Bopp, Wilcox, Oberrecht, Kammermann, & McElmurray, 2004;Melton, Marshall, Bland, Schmidt, & Guion, 2013). Compared to women living in urban areas, rural women have conveyed more caregiver duties and more discouragement from others as barriers to physical activity (Wilcox et al, 2000).…”
mentioning
confidence: 99%